A 3D microfluidic chip for electrochemical detection of hydrolysed nucleic bases by a modified glassy carbon electrode - Vlachova, Jana; Tmejova, Katerina; Kopel, Pavel; Korabik, Maria; Zitka, Jan; Hynek, David; Kynicky, Jindrich; Adam, Vojtech; Kizek, Rene (Sensors (Basel, Switzerland), 2015)
Modification of carbon materials, especially graphene-based materials, has wide applications in electrochemical detection such as electrochemical lab-on-chip devices. A glassy carbon electrode (GCE) modified with chemically alternated graphene oxide was used as a working electrode (glassy carbon modified by graphene oxide with sulphur containing compounds and Nafion) for detection of nucleobases in hydrolysed samples (HCl pH = 2.9, 100 °C, 1 h, neutralization by NaOH). It was found out that modification, especially with trithiocyanuric acid, increased the sensitivity of detection in comparison with pure GCE. All processes were finally implemented in a microfluidic chip formed with a 3D printer by fused deposition modelling technology. As a material for chip fabrication, acrylonitrile butadiene styrene was chosen because of its mechanical and chemical stability. The chip contained the one chamber for the hydrolysis of the nucleic acid and another for the electrochemical detection by the modified GCE. This chamber was fabricated to allow for replacement of the GCE.